Language, space and the Bible: How to create (things) with words - Branimir Vukosav; Arkadiusz Krasicki; Marijana Kresić Vukosav (Nova Prisutnost)
The paper discusses human possibilities and limitations with respect to the creative function of language, by analysing linguistic, geographic and theological accounts of how human identity and the world are created in and through language. In a first step we will discuss realistic vs. constructivist approaches in epistemology, with the aim of describing the shift towards postmodernist and relativistic scientific positions, especially in research in the fields of linguistics and geography. Then, we analyse the creative functions that these disciplines attribute to language use, including speech acts and geographic names. The theological part of the paper focuses on the creative power of God, as it is described in the Holy Bible and expressed through language, with reference to the allegory of Babel. In this section, God’s creation is put in contrast to human creation. The study concludes with a synthesis of all insights gained and a comparison of human vs. the divine power of creation.